Implications of The SKMHT Validity Period According to The Term of Subsidized Home Finance in Connection With The Principle of Lex Superior Derogat Legi Inferiori - Mardiana, Fitri; Sri Darmadi, Nanang (TABELLIUS: Journal of Law, 2024)
Regulation of the Minister of Agrarian Affairs of the Head of BPN No. 22/2017 Concerning the Determination of the Time Limit for the Use of a Power of Attorney to Encumber Mortgage Rights to Guarantee the Settlement of Certain Credits, if the regulation of the ATR/BPN ministry is enforced, there will be a conflict of norms between Law Number 4 of 1996 concerning Mortgage Rights and the regulation of the ATR/BPN ministry. Regulation of the ATR/BPN ministry number 22 of 2017 overrides the Mortgage Rights Law in terms of the limitation of the SKMHT period. The principle of Lex Superior Derogat Legi Inferiori states that lower regulations must not conflict with higher regulations. Regulations with lower authority should not exceed higher regulations. The purpose of this study is to analyze the effect of changes in SKMHT regulations in subsidized housing financing based on the principle of lex superior derogate legi inferiori. This research method is a normative legal research method. The approach in this study uses a case approach and a legislative approach. The data required includes secondary data consisting of the 1945 Constitution; Law Number 10 of 1998; Law Number 21 of 2008;Law Number 12 of 2011,  Law Number 4 of 1996; Regulation of the Minister of Agrarian Affairs of the Head of BPN No.22/2017; Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 35 of 2021, as well as books and other supporting documents. Taken with the method of data collection using library techniques. The data analysis method is prescriptive. Based on the research, it was concluded that the conflict of legal norms occurred due to differences in the regulations regarding the period of use of SKMHT between the Mortgage Rights Law and Regulation of the Minister of ATR/BPN No. 22 of 2017. The Mortgage Rights Law regulates the maximum period of SKMHT for 3 months, while Regulation of the Minister of ATR/BPN No. 22 of 2017 regulates that the period of SKMHT can be valid during the credit period or until the end of the principal agreement. The Mortgage Rights Law as a law has a higher degree compared to the Regulation of the Minister of ATR/BPN which is an implementing regulation. Therefore, based on the principle of lex superior derogate legi inferiori, the regulations in the Mortgage Rights Law should apply.